PEMENUHAN DIMENSI-DIMENSI PELAYANAN PUBLIK DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN MINAHASA UTARA - Sinsu, Christanto; Mandey, Jantje; Plangiten, Novva (JURNAL ADMINISTRASI PUBLIK, 2016)
Abstrac : Public service is the right of every citizen that must be given by the government. But the fact is the one who should serve the citizens haven’t done it well. It seems that they still don’t have much concern about their responsibility moreover, their (government employees’ or civil official’s) accountability still can’t be accounted for even to their leader in terms of public serving. Because they still have some significant problem.This research uses qualitative research methods, descriptive. Informant research by as much as 10 (ten) informant: 1 person head of Department, 1 Secretary, 1 head of the sub. the General section and the staffing, 1 civil State apparatus, 3 people community. data collection techniques used i.e., interview techniques, techniques of observation/observation, and technical documentation. data analysis techniques used, namely the reduction of data, data presentation, and conclusion.Key words : The accomplishment of dimension, Public Service